2015
DOI: 10.1186/s13063-015-0804-0
|View full text |Cite
|
Sign up to set email alerts
|

BEWARE: Body awareness training in the treatment of wearing-off related anxiety in patients with Parkinson’s disease: study protocol for a randomized controlled trial

Abstract: BackgroundThe wearing-off phenomenon in patients with Parkinson’s disease (PD) is a complication of prolonged levodopa usage. During this phenomenon, motor symptoms such as rigidity and freezing re-emerge. This is often accompanied by non-motor symptoms, including anxiety, the so-called wearing-off related anxiety (WRA). Current treatment options are limited and typically focus on either the physical or mental aspects of wearing-off. An integrated approach seems warranted in order to optimally address the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A recent six-week group mindfulness intervention involving lifestyle management strategies for PD patients showed a significant reduction in depression and stress, and improvements in mindfulness and ADL at sixmonth follow-up (Advocat et al, 2016). In-person ACT-based interventions for wearing-off related anxiety (Dissanayaka et al, 2016b) associated with prolonged dopamine-replacement therapy in PD are currently underway (Ghielen et al, 2015). These promising findings support the future adaptation of such psychological interventions for flexible, home-based delivery, thereby increasing telehealth-based treatment options for PD patients beyond CBT, and enhancing patient-centerd care.…”
Section: Future Directions For Telehealth In Pdmentioning
confidence: 99%
“…A recent six-week group mindfulness intervention involving lifestyle management strategies for PD patients showed a significant reduction in depression and stress, and improvements in mindfulness and ADL at sixmonth follow-up (Advocat et al, 2016). In-person ACT-based interventions for wearing-off related anxiety (Dissanayaka et al, 2016b) associated with prolonged dopamine-replacement therapy in PD are currently underway (Ghielen et al, 2015). These promising findings support the future adaptation of such psychological interventions for flexible, home-based delivery, thereby increasing telehealth-based treatment options for PD patients beyond CBT, and enhancing patient-centerd care.…”
Section: Future Directions For Telehealth In Pdmentioning
confidence: 99%
“…As a result, multidisciplinary rehabilitation programs that support functionality and include cognitivebehavioral strategies and approaches for secondary effects due to fear of falling, balance, physical activity level, and kinesiophobia may be beneficial for Parkinson's patients to reduce the negative effects of kinesiophobia and the perceived level of disability. Acceptance and commitment therapy-based exercise programs such as BEWARE, which are currently being studied, may also be beneficial in reducing kinesiophobia in patients with PD (Ghielen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other trials for therapy involving body awareness training for the treatment of wearing off-related anxiety and a mindfulness-based exercise have shown that these modalities are helpful in balance and well-being. 32,33 Serial electroconvulsive therapy (ECT) has not been well studied but was found to be effective in a case study of severe anxiety in patients with PD. 34…”
Section: Management Of Anxiety In Pdmentioning
confidence: 99%